The Effect of Maternal SARS-CoV-2 Infection on Neonatal Outcome - Melinda Matyas; Madalina Valeanu; Monica Hasmasanu; Bianca Voina; Adelina Tutu; Gabriela C. Zaharie (MDPI AG, 2023)
(1) Background: Neonates born to SARS-CoV-2 positive mothers are at risk of infection, as well as adverse outcomes due to the infection. The aim of our study was to analyze the impact of maternal SARS-CoV-2 infection on neonatal outcome. (2) Methods: We conducted a prospective, longitudinal study. We collected data on maternal symptomatology upon admission and their correlation with the development of the infant. Through a questionnaire we analyzed the impact on breastfeeding of the separation of the mother from the newborn, as well as the maternal psycho-emotional effect. (3) Results: Ninety infants were enrolled in the study, from one twin pregnancy and the rest singleton pregnancies. Out of the 89 mothers, 34 showed symptoms. Neonates from mothers with anosmia and ageusia had a higher value of WBC and lymphocytes (p = 0.06 and p = 0.04). Breastfeeding was started in 57.3% of mothers after their discharge from hospital and only 41.6% of the whole study group continued at the follow-up visit. Mothers who described a negative experience during hospitalization associated a 2.42 times higher risk of not continuing breastfeeding. (4) Conclusion: None of the infants enrolled in the study had SARS-CoV-2 infection either at birth or within the first two months of life. Breastfeeding was started with more than half newborns after discharge from hospital. The negative experience generated by the separation from their babies influenced breastfeeding.